2003
DOI: 10.1034/j.1600-0773.2003.920107.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Toxic Effect of Amiodarone in Rats

Abstract: Amiodarone is an antiarrhythmic drug now more frequently used after a number of years in which the use had been on the decline due to a number of studies which reported side effects such as chronic toxicity, primarily in the lungs, liver and thyroid glands. Additionally, in some patients an increase in serum creatinine was noted, however the effect of amiodarone on renal function had never been closely examined. Thus, the aim of our study was to analyse the effects of amiodarone on renal function in rats. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
2
14
0
1
Order By: Relevance
“…In kidneys, reduced CL CR was observed in amiodarone-administered animals. This result complies with the described impairment of kidney function during acute amiodarone therapy [36]. Nevertheless, a decreased glomerular filtration rate after administration of amiodarone was not associated with reduction of MTX CL R .…”
Section: Discussionsupporting
confidence: 90%
“…In kidneys, reduced CL CR was observed in amiodarone-administered animals. This result complies with the described impairment of kidney function during acute amiodarone therapy [36]. Nevertheless, a decreased glomerular filtration rate after administration of amiodarone was not associated with reduction of MTX CL R .…”
Section: Discussionsupporting
confidence: 90%
“…Amiodarone, an iodine-rich antiarrhythmic agent, can cause both hypothyroidism and hyperthyroidism (125,126), as well as acute renal damage (127). As mentioned before, rifampicin can cause tubulointerstitial nephritis and hyperthyroidism (73).…”
Section: Drugs In Thyroid and Renal Diseasesmentioning
confidence: 99%
“…The amiodarone-induced inhibition of tacrolimus metabolism resulted in significantly lower doses of tacrolimus necessary to achieve proper therapeutic serum concentrations [3]. Much less is known about effects of tacrolimus on possible elevation of amiodarone concentration, which may be clinically important while both animal and observational studies suggested that amiodarone may cause renal impairment by reducing renal blood flow or inducing tubular alterations [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have described QT interval prolongation after concomitant use of amiodarone and tacrolimus [2,3]. Also, amiodarone nephrotoxicity has been demonstrated in animal and observational studies [4][5][6]. We report a case of kidney allograft dysfunction possibly caused by amiodarone nephrotoxicity precipitated by tacrolimus.…”
Section: Introductionmentioning
confidence: 97%